Enhancement of Legal Framework to Combat Cybercrime in the Age of Disruption - Shereen KHAN; Nasreen KHAN; Olivia TAN; Swee Wei TAN (Communications of International Proceedings, 2020)
One of the priorities of the ‘National Policy’ on Industry 4.0 is to holistically and rapidly transform industry strength of Malaysia in both a comprehensive and accelerated way and an integral component is the adoption of appropriate legislation against the misuse of ICTs for criminal purposes. The study shows that Malaysia’s possible economic loss from cybercrime with the financial sector hitting its worst, it could hit a record of US$ 12.2 billion. With the advent of technology, cybercrime is increasing and it can be interpreted from the figures that either in investigation or legislation, there is something which needed to be looked into. Currently, the legislation on cybercrimes are in piece meals and Malaysia needs a comprehensive cybercrime legislation in order to achieve a good prosecution in cybercrime cases. Thus, the purposes of this study are to find out why existing law is ineffective, and examine on how other jurisdictions deal with cybercrime. Therefore, the main aim is to propose a comprehensive new law to tackle cybercrime effectively and efficiently. Both quantitative and qualitative analysis will be used in this study. In addition to conducting a comprehensive analysis by reviewing the laws in other selected jurisdictions, selected interviews with relevant government departments, nongovernmental organisations and legislatures will be conducted. A revised criminal policy aimed at protecting society from cybercrime, through the implementation of relevant legislation, needs to be followed as a matter of priority. Ineffective legislative framework results in encouraging criminals to conduct criminal cyber activities.
Keywords: Cybercrime; Legislation; Disruption